Mid Term Review of the Seventh Malaysia Plan 1996-2000 Speech by The Prime Minister in the Dewan Rakyat, 22 April 1999 (1999)
Address by The Prime Minister Y.A.B. Dato' Seri Dr. Mahathir bin Mohammad Introducing the Motion to Table The Mid-Term Review of the Seventh Malaysia Plan in Dewan Rakyat on Thursday, 22 April 1999 at 11.00 a.m.
also published in Malay Language
Keywords: Economic Forecasting -- Speech -- Malaysia